A Review of the ACID Synthetic Aperture Sonar and other Sidescan Sonar Systems - Riyait, V. S.; Lawlor, M. A.; Adams, A. E.; Hinton, O. R.; Sharif, B. S. (The International Hydrographic Review, 2015)
The ACID project was part of the MAST Programme and was funded by the European Communities, to develop a synthetic aperture sonar for high resolution mapping of the seafloor. The collaboration of several European Institutions has enabled the ACID synthetic aperture sonar to be developed and tested during sea trials in May 1993. This paper discusses how the ACID synthetic aperture sonar system fits into the existing field of conventional sidescan sonar systems and the potential advantages to be gained using synthetic aperture processing techniques. The main advantage of the ACID sonar is that its azimuth resolution is independent of range and of the transmitted signal frequency. Sonar designers can, therefore, use lower operating frequencies and still obtain high azimuth resolutions. However, this paper also highlights the need for developing techniques which can increase the area mapping rate of synthetic aperture sonars which is essentially limited by the azimuth sampling constraint. Images from sea trials during May 1993 are presented which show areas of the seafloor before and after synthetic aperture sonar processing.